Assessment of the Stability of the KL Sultan Hasanuddin Ship During Passenger Evacuation - Bustamin, Bustamin; Darwis, Darwis; Noegraha, Andi Dirga (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2025)
KL. Sultan Hasanuddin previously used only as a training ship for cadets, currently operates as a public passenger transport vessel in the islands and ports of South Sulawesi. The objective of this study is to measure the extent of the effect of changes in the stability of the KL. Sultan Hasanuddin vessel during passenger evacuation in the event of a fire, in accordance with IMO Regulation A.749(18) Chapter 3. One of the factors that significantly influences vessel stability is cargo distribution, including passenger distribution behavior. When passengers move freely on the ship, such as walking from one place to another, running, or gathering in a specific area, this causes a shift in the ship's center of gravity. The method used in this study is the Krylov method to obtain the ship's GZ stability curve by dividing several cases and conditions of the ship's tanks. Based on the simulation and analysis results, changes in the stability of the KL. Sultan Hasanuddin ship were observed during passenger evacuation when the ship departed from the port (departure), with a 18% decrease in the GZ value; during the voyage (seagoing), with a decrease in the GZ value reaching 58%; and upon arrival at the port (arrival), with a decrease ranging from 44% to 70%.